HUBUNGAN ANTARA KARAKTERISTIK DEMOGRAFI PEKERJA, BEBAN KERJA MENTAL, DAN GAYA KEPEMIMPINAN TERHADAP BURNOUT PADA STAFF ADMINISTRASI FKM UNDIP - Mutiara Putri Masduki; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Burnout is physical, mental, and emotional exhaustion that occurs continuously which causes a person to lose motivation at work until appears the behavior of withdrawing from work to the desire to stop working, burnout is also caused by a mismatch between job demands and the rewards received. In carrying out work, it is not uncommon for workers to experience physical or mental exhaustion to experience prolonged stress. This prolonged stress is also known as burnout. Burnout sufferers are often found in public service workers such as teachers, police, nurses, and administrative workers are no exception. Administrative staffs are quite vulnerable to burnout because administrative staffs are required to work calmly, carefully, thoroughly, and able to work with a team. The factors that influence burnout consist of internal and external factors. Internal factors consist of demographic characteristics (age, gender, marital status, education, and years of service), personal characteristics (personality characteristics), and the attitude of how a person responds to his work (job attitude). Meanwhile, external factors consist of job characteristics, occupational characteristics, and organizational characteristics. The purpose of this study was to determine the relationship between the demographic characteristics of workers (age, gender, marital status, education, years of service), mental workload, and leadership style on burnout. This research is a quantitative correlation study using a cross sectional design. The population of this study is the administrative staffs of Faculty of Public Health Diponegoro University with the sampling technique used is total sampling and the data analysis used is univariate and bivariate analysis. The result of this study is that there are no significant relationship between age, gender, marital status, education, years of service, mental workload, and leadership style with burnout.